Pengaruh Motivasi dan Budaya Organisasi terhadap Kinerja Karyawan pada Pdam Tirta Intan Cabang Utama Garut Kota Kabupaten Garut - Hedi Cupiadi (Jurnal Wacana Ekonomi, 2016)
The purpose of this study was to determine the influence of Motivation and Organizational Culture on Employee Performance at PDAM Tirta Intan Main Branch of Garut Kota. The research method used in this research is quantitative descriptive analysis method. The study population was 76 employees with a permanent status with a census sampling technique. The data collection techniques used were documentation study and field study through observation, interviews and questionnaires. The data analysis technique used to answer the hypothesis of this study is statistical analysis with multiple linear regression models. Based on the research results, the implementation of motivation, organizational culture and employee performance at PDAM Tirta Intan Main Branch of Garut Kota has been good. The results of hypothesis testing both partially and simultaneously show that the motivation and organizational culture variables have an effect on employee performance.